2021
DOI: 10.2147/jep.s323962
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin Modulates miR-223-3p and NF-κB Levels in the Pancreas of Rat Model of Polycystic Ovary Syndrome to Attenuate Autophagy Flare, Insulin Resistance and Improve ß Cell Mass

Abstract: Purpose Polycystic ovary syndrome (PCOS) is a prevalent female endocrine disorder. 50–70% of PCOS patients suffer from glucose intolerance, insulin and β cell impairments. Updated studies reveal the crucial regulatory role of inflammation modulators in various diseases, by manipulating autophagy and oxidative stress. However, the data available about autophagy in PCOS pancreas, especially in relation to inflammation key players are little. This study investigated pancreatic autophagy status in PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“… 31 , 39 Moreover, this process enhances the therapeutic activity of promising compounds through improving their solubility and adequate delivery. 22 , 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 39 Moreover, this process enhances the therapeutic activity of promising compounds through improving their solubility and adequate delivery. 22 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…31,39 Moreover, this process enhances the therapeutic activity of promising compounds through improving their solubility and adequate delivery. 22,40 Therefore, in this study, we formulated SIM in a SIM-CB formula. We tested the cytotoxic activity of free SIM and SIM-CB on MCF-7 cells and investigated ferroptosis as a possible additional mechanism contributing to SIM anticancer actions.…”
Section: Discussionmentioning
confidence: 99%
“…Although miR-223-3p is reported to serve as a sponger of long noncoding RNAs or circular RNAs in a wide variety of Evidence-Based Complementary and Alternative Medicine disease models, several studies have demonstrated that miR-223-3p can be regulated by the extraction of Chinese herbal medicine. For instance, nanocurcumin dampens insulin resistance and autophagy flare with improved β cell mass via regulating miR-223-3p and NF-κB levels in the pancreas of a rat model of polycystic ovary syndrome [35]. Icariin regulates the miR-223-3p/NLRP3 signaling axis to relieve rheumatoid arthritis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the different actions of emodin in these studies are that the relative prevalence of autophagy differs in discreet tissues (kidney and intestine) in energy metabolic processes, and exogenous factors (for example, nutritional status of foods used in the experimental model including amino acids, fatty acids, and glucose) may cause different changes in autophagy regulation. Additionally, in the rat with polycystic ovary syndrome, nanocurcumin functions to upregulate miR‐223‐3p in pancreatic tissues contributing to ameliorating insulin resistance by suppressing autophagy activity as confirmed by dramatic decline in LC3‐II and p62 proteins (Abuelezz et al., 2021). In summary, the current data provide new mechanistic insights into possible contribution of miRNAs regulated by polyphenols involved in maintaining autophagy.…”
Section: Possible Mechanisms Of Polyphenol‐meditated Autophagy In Glmdsmentioning
confidence: 99%